2018
DOI: 10.3390/ijerph15040717
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Services and Their Initiatives to Improve the Care of Indigenous Australians

Abstract: Indigenous Australians continue to experience significantly poorer outcomes from cancer than non-Indigenous Australians. Despite the importance of culturally appropriate cancer services in improving outcomes, there is a lack of awareness of current programs and initiatives that are aimed at meeting the needs of Indigenous patients. Telephone interviews were used to identify and describe the Indigenous-specific programs and initiatives that are implemented in a subset of the services that participated in a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…Surveys were completed for 58 of 125 public cancer treatment centres. Based on findings from the survey, follow-up interviews were conducted with 14 service providers to explore current practice and programs aimed at improving cancer care for Indigenous Australians [ 34 ]. Finally, centres which reported promising practices were identified, with four services participating in detailed case studies around their specific practices and innovations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surveys were completed for 58 of 125 public cancer treatment centres. Based on findings from the survey, follow-up interviews were conducted with 14 service providers to explore current practice and programs aimed at improving cancer care for Indigenous Australians [ 34 ]. Finally, centres which reported promising practices were identified, with four services participating in detailed case studies around their specific practices and innovations.…”
Section: Methodsmentioning
confidence: 99%
“…This article presents Indigenous workforce strategies from two cancer services and their affiliated hospitals. The services were identified in a multi‐stage, national study as particularly high performing and innovative in their provision of cancer services for Indigenous cancer patients and their families [ 33 , 34 ]. The cancer services are both within public tertiary teaching hospitals, however are vastly different with respect to rurality, management and patient cohort, as summarised in Table 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the problem of disproportionately higher cancer mortality among Indigenous populations has been reported in other parts of the world, too 46–49 . A study from Western Australia 50 stressed the need for a trained workforce with effective cross‐cultural communication skills, providing best practice care and improving the knowledge, attitudes and understanding of cancer by Indigenous people as a potential way forward. Another study from Queensland 51 identified key areas of attention to ensure the success of any intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Providing cancer treatment services that meet the needs of Indigenous patients is a critical element in improving outcomes 23,24 . While evidence suggests that many mainstream cancer treatment centres and support services are currently failing to provide accessible, culturally appropriate cancer care to Indigenous Australians, 20,23,25–27 reports are starting to emerge of cancer services that are providing innovative services to engage Indigenous patients and their families 28–30 . However, there has been limited formal evaluation of such initiatives or the extent to which they occur in cancer services around Australia.…”
mentioning
confidence: 99%
“…The lack of information makes it challenging to build a complete and accurate picture of what cancer services are currently being provided to Indigenous Australians, who is providing those services and where the service gaps are. It is also difficult for cancer service providers to learn from one another about successful programs and initiatives for Indigenous cancer patients and their families 28 …”
mentioning
confidence: 99%